Features of the manifestation of arterial hypertension in patients with a new coronavirus infection - T. D. Solnceva; A. A. Lachugin; O. A. Sivakova; I. E. Chazova (Евразийский Кардиологический Журнал)
The purpose. Assessment of the presence of the cardiovascular risk factors, associated clinical conditions, the degree of target organ damage in patients with arterial hypertension depending on the new coronavirus infection.   Material and methods. In a retrospective cohort study 284 patients with arterial hypertension were identified, 162 of them had a novel coronavirus infection and 122 patients didn’t have a history of a new coronavirus infection. Patients who had a new coronavirus infection were divided into groups depending on the disease. Inclusion criteria were the presence of arterial hypertension in history and taking antihypertensive therapy.   Results. Patients with hypertension who’ve had a new coronavirus infection are more likely to have risk factors such as smoking, overweight, early menopause as opposed to patients with hypertension without indication of past COVID-19. Comparing patients with increased severity of the novel coronavirus infection elevated uric acid levels and hypercholesterolemia were associated with more severe COVID-19 (p < 0.05). Patients with chronic kidney disease, cerebrovascular disease, detection of atherosclerotic lesions of the brachiocephalic arteries and diabetes mellitus have an increased probability of deaths occur from the novel coronavirus infection (p < 0.05). There was no significant difference between the compared groups of coronary heart disease, atrial fibrillation, chronic heart failure and also the daily blood pressure profile and a severe course of COVID-19.   Сonclusion. The presence of diabetes mellitus, cerebrovascular disease, chronic kidney disease, detection of atherosclerotic lesions of the brachiocephalic arteries, and also hyperuricemia or hypercholesterolemia in patients with hypertension revealed a risk of severe coronavirus infection.